Modern plains vizcacha (Lagostomus maximus, Chinchillidae, Rodentia) as a bone accumulating agent in the Argentine Pampas: Application to the study of fossiliferous sites. (February 2019) - Tomassini, Rodrigo L.; Montalvo, Claudia I.; Fernández-Jalvo, Yolanda; Garrone, Mariana C.; Kin, Marta S.
Abstract: Lagostomus maximus (Rodentia, Chinchillidae), or Plains vizcacha, is a caviomorph rodent that inhabits semi-arid grasslands and desert scrub of central and northern Argentina, southern Paraguay and southeastern Bolivia. A particular behavior of the Plains vizcacha is the collection and transport of bones, dried dung and branches, among other objects, which are accumulated near the vizcacheras entrances. A bone concentration, originated in active vizcacheras of the southwestern Buenos Aires Province (Argentina), was studied from a taphonomic point of view for one year. The obtained results reflect that Plains vizcacha represents an important bone accumulating agent in the Argentine Pampas, and it is capable of producing large concentrations. Moreover, their vizcacheras act as natural traps that may favor the accumulation and preservation of the bone remains. The information obtained through this actualistic study provides new information on the ecology of this rodent and, in turn, introduces a framework of reference for the identification of similar concentrations in the fossil record. Highlights: An actualistic taphonomic study was performed in an active modern vizcacheral Plains vizcacha is an important bones accumulator agent. The vizcacherales represent an environmental context with a high biodiversity. Vizcacheras act as natural traps that favor the preservation of bones.